RBP4 Is Associated With Insulin Resistance in Hyperuricemia-Induced Rats and Patients With Hyperuricemia - Liu, Chan; Zhou, Xiao-Rong; Ye, Mu-Yao; Xu, Xiang-Qing; Zhang, Yu-Wei; Liu, Hong; Huang, Xian-Zhe (Frontiers in Endocrinology, 2021)
Objective: Hyperuricemia (HUA) is strongly associated with abnormal glucose metabolism and insulin resistance (IR). However, the precise molecular mechanism of HUA-induced IR is still unclear. Retinol binding protein 4 (RBP4) has been shown to induce IR in type 2 diabetes mellitus. This study was designed to clarify the relationship between RBP4 and HUA-induced IR and its potential mechanisms. Methods: Patients with HUA were collected to detect the levels of plasma RBP4 and clinical biochemical indicators. Rats were fed with 10% high yeast and oteracil potassium (300 mg/kg) via intraperitoneal injection once daily for eight weeks, and gavage with adenine (100 mg/kg) once daily from the fifth week to induce the HUA model. Glucose consumption testing was performed to determine the capacity of glucose intake and consumption in 3T3-L1 adipocytes. Real-time polymerase chain reaction (RT-PCR) and western blot were used to detect the mRNA and protein level of RBP4 and insulin receptor substrate-phosphatidylinositol 3-kinase-active protein kinase (IRS/PI3K/Akt) signaling pathway-related proteins. Results: The levels of plasma RBP4 in both HUA patients and HUA rat models were significantly higher than that in the control groups. The level of plasma RBP4 was positively correlated with plasma uric acid, creatinine, fasting insulin, IR index, total cholesteroland triglyceride levels in patients with HUA. In HUA rats, the level of plasma RBP4 was positively correlated with plasma uric acid, IR index, and triglycerides. HUA rats also exhibited IR. After inhibition of RBP4 expression, the phosphorylation level of the IRS/PI3K/Akt signaling pathway increased, and IR was significantly improved. Conclusion: HUA induced IR both in vitro and in vivo. RBP4 may be involved in HUA-induced IR by inhibiting IRS/PI3K/Akt phosphorylation. Our findings may provide a new insight for the treatment of IR caused by HUA.